Trollhätte kanals slusskapacitet - En studie utifrån geografiskt lämpliga aktörers produktionsvolymer - Johansson, Henrik; Torelund, Martin (My University, 2015)
E2015:115, This study was designed when the “Traffic office in Gothenburg” desired to overhaul the possibilities to increase the traffic along Göta river. The cargo flow in the river has because of this decreased constantly during a long time. Furthermore, the project went from being focused on ho further goods could be attracted; to affect the capacity of the fairway between Gothenburg and La Vänern. The aim of the project has been to evaluate the lock capacity for the fairway. The capacit has been presented through various scenarios based on eight selected operators’ production volum by Vänern. The study has been based on a survey in which three key parts, Trollhätte channel, Port of Gothenburg and the ports by Lake Vänern has been explained. The selected operators have also been mapped about their production volumes in this part. The survey’s collected data has formed the basis for both calculations and evaluations. According to the study’s calculations, it has been established that the fairway possesses a really high capacity, which is currently unused. Calculations also show that all eight operators totally exported volume, would be about a fourth of the total capacity of the fairway. In addition to this, i has been established that the river at a possible reconstruction of the locks could have an even higher capacity. The study indicates that companies around Lake Vänern don’t use much maritime transportation, since it’s not considered to be sufficiently attractive in the area. The report also describes what could be improved for a possible redevelopment and the potential problems that could occur at the possible closure of the locks.
Keywords: Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics; Transport